Respostas

2013-04-22T12:40:03-03:00

A:  2m²+5m+3-4m²-2m+1=
      Coloque os números que contém " M" antes do " = " e os números normais depois dele. 
     
       2m²+5m-4m²-2m= -3-1 
       4m+ 5m- 16m-2m=  -4
        9m-16m-2m= -4
                 -7m-2m= -4
                        - 9m= -4   (*1_
                            9 m= 4
                               m= 9/4
                                m= 2,25

B:    4m² -2m +1 - (-3m²)-m+3=
        4m² - 2m+ 3m² -m = -1-3
        16m -2m +9m - m= -4
         14m+ 9m-m = -4
                23m-m= -4

                     22 m=-4
                           m= - 22/4
                            m= - 5,5


C: -3m² - m + 3 - 2m² + 5m +3 =
     -3m² - m- 2m² + 5m = -3 -3
     -6m-  m - 4m + 5m= -6
     -7m - 4m +5m= -6
           -11 m +5m = -6
                      - 6m = -6 (*1)
                           m= 6/6
                           m= 1
                                 

1 5 1